Home and Horticultural Pests - Bagworms - Bauernfeind, Robert J. (My University, 1999)
This publication describes bagworms and how to manage this pest of shrubs and trees.
MF728_1999_05
Keywords: MF728; Insects; Forestry; Home and Family; MF